Testing The Normality Of Residuals On Regression Model For The Growth Of Moraxella Sp. B On Monobromoacetic Acid - Shamaan, N.A.; Shukor, M.S.; Masdor, N.A.; Sabullah, M.K.; Shukor, M.Y (Parlar Scientific Publications, 2024)
Bulletin of Environmental Science and Sustainable Management BESM, 2015, Vol 3, No 1, 16-18